Heat-related illnesses among workers in latex glove industry under heat stress condition - Mohd Kassim, Nurazirah (2019)
Malaysia is the world largest producer of latex glove. Glove production involved work processes with high temperature. However, less study has been conducted on the hazards of high temperature among the workers here. Thus, this study was conducted to evaluate the heat-related illnesses and physiological changes among latex glove industry workers under heat stress condition. This cross-sectional study was conducted in a glove factory at Negeri Sembilan. This location was selected based on the highest number of workers in Negeri Sembilan which are 350 workers and the highest daily production rate. The respondents were randomly selected from the list name provided. Total workers (n=88) were interviewed using questionnaire adopted from previous study. The adopted questionnaire includes the socio demographic, occupational, lifestyle, health and heat-related illnesses information of respondents. Heat stress assessment (WBGTin) and the level of air velocity were measured using QUESTTemp°34 Thermal Environment Monitor and TSI Velocicalc®Air Velocity Meters respectively. The Personal heat monitor was used to monitor the level of personal body temperature of workers. Omron MC-510 Gentle Temperature ear thermometer (measure core body temperature), POLAR Heart Rate FT60 (measure heart rate) and OMRON T3 Automatic Blood Pressure Monitor (measure blood pressure) were used in the physiological changes measurement of the workers. All of these psychological parameters were taken in three sessions; before the shift, after 2 hours working and after 8 hours working. The result were exceeded Threshold Limit Value (TLV) (>28oC) in the productionarea. The highest prevalence of heat-related illnesses on respondents was dehydration (81.8%), followed by heat exhaustion (80.7%), heat cramps (26.1%), heat rashes (26.1%), heat stroke (9.1%) and the heat syncope (6.8%). Based on this study there is a statistically significant correlation between personal heat and prevalence of heat-related illnesses (r=0.54, p<0.05). The chi-square test results revealed that only duration of employment (X2=3.475, p<0.01) are significantlyassociated with prevalence of heat-related illnesses reported. the multivariate logistic regression shows that only the personal heat had a significant association with prevalence of heat-related illnesses. The prevalence of heat-related illnesses was measured using the questionnaire. The ANOVA was statistically significant between physiological parameter (core body temperature F= 281.10, P<0.001); heart rate, (F=237.86, p<0.001); and blood pressure, (F= 194.43, p<0.001) and three work session. As a conclusion, the workers in glove industry are exposed to high level of heat stress. All the three physiological parameters (core temperature, heart rate and blood pressure) of respondent data show that there were changed through three periods of time. The air velocity at majority work sections in production area was exceeded the baseline given for the specify temperature. The highest prevalence of heat-related illness on respondents was dehydration, followed by heat exhaustion, heat cramps, heat rashes and heat stroke. This shows that the glove industry expose workers to heat stress which directly causing workers to get heat-related illness. Personal protective equipment such as cool vest also helps in protection from hot working environment. The training on heat stress in the way of control heat stress should be provided by employers which help in educating and create awareness among workers on the symptoms of heat-related illness.